2020
DOI: 10.3389/fpls.2020.00346
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Yield Potential of Mesoamerican Wild Common Beans From Contrasting Eco-Geographic Regions by Nested Recombinant Inbred Populations

Abstract: Genetic analyses and utilization of wild genetic variation for crop improvement in common bean (Phaseolus vulgaris L.) have been hampered by yield evaluation difficulties, identification of advantageous variation, and linkage drag. The lack of adaptation to cultivation conditions and the existence of highly structured populations make association mapping of diversity panels not optimal. Joint linkage mapping of nested populations avoids the later constraint, while populations crossed with a common domesticated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 127 publications
0
16
0
Order By: Relevance
“…Parallel to the unique shoot morphology, phenology, molecular characteristics, and allelic frequencies that exist across different gene pools and races, differences in root phenotypes would likely have similarly emerged through multiple domestication events within distinct ancestral populations and have been maintained by the self‐pollinating nature of this species, as well as the geographical separation of these groups (Chacón, Pickersgill, & Debouck, 2005; Debouck & Tohme, 1989; Gepts, 1988; Gepts & Debouck 1991; Singh, Gepts, & Debouck, 1991). Although the present work only focuses on domesticated genotypes, because wild populations participated in initial domestication of this species in different regions (Blair, Soler, & Cortes, 2012), it could be that the observed gene pool and race differences in root architecture closely parallel those found in wild accessions along their geographical range of distribution (Berny Mier y Teran et al., 2019; Berny Mier y Teran, Konzen, Palkovic, Tsai, & Gepts, 2020).…”
Section: Discussionmentioning
confidence: 96%
“…Parallel to the unique shoot morphology, phenology, molecular characteristics, and allelic frequencies that exist across different gene pools and races, differences in root phenotypes would likely have similarly emerged through multiple domestication events within distinct ancestral populations and have been maintained by the self‐pollinating nature of this species, as well as the geographical separation of these groups (Chacón, Pickersgill, & Debouck, 2005; Debouck & Tohme, 1989; Gepts, 1988; Gepts & Debouck 1991; Singh, Gepts, & Debouck, 1991). Although the present work only focuses on domesticated genotypes, because wild populations participated in initial domestication of this species in different regions (Blair, Soler, & Cortes, 2012), it could be that the observed gene pool and race differences in root architecture closely parallel those found in wild accessions along their geographical range of distribution (Berny Mier y Teran et al., 2019; Berny Mier y Teran, Konzen, Palkovic, Tsai, & Gepts, 2020).…”
Section: Discussionmentioning
confidence: 96%
“…This is because they have become adapted to such environments. A recent study on Mesoamerican common bean showed that wild relatives of the crop collected from dry areas of South America are found to be good sources of drought tolerance (Teran et al, 2020). Some wild cowpea lines are characterized by perennial growth habit and this attribute could also contribute to drought tolerance as they retain their greenness, and are able to survive from one cropping season to another through the intervening dry season.…”
Section: Drought Tolerancementioning
confidence: 99%
“…The F 1 plants derived from this cross exhibited partial sterility due to a low number of fertile pollen grains. In common bean (Phaseolus vulgaris L.), a grain legume with 11 pairs of chromosomes and a member of Phaseolinaea as cowpea, inbred populations were developed from three wild x domesticated backcrosses (Teran et al, 2020). The BC 1 S 4 populations were evaluated in the fields located at three environments comprising two fully irrigated trials during two cropping seasons and an imposed terminal drought in the second season.…”
Section: Development Of Populations With Introgressions From Cwrs: Inmentioning
confidence: 99%
See 1 more Smart Citation
“…MIR1511 deletion occurred in genotypes originating from the northern and southern extreme limits of the common‐bean distribution in the Latin American area. Such a distribution pattern correlates with the annual precipitation pattern reported for the American continent (Ariani et al ., 2018; Harris et al ., 2020), indicating that genotypes with MIR1511 deletion originated from areas with significantly less precipitation as compared with areas where genotypes with unaltered MIR1511 originated (Ariani et al ., 2018; Berny Mier y Teran et al ., 2020; Harris et al ., 2020). Drought makes soil not suitable for agriculture; it tends to increase soil concentration of different compounds that would result in plant toxicity, including AlT, which is an important plant growth‐limiting factor (Schier and McQuattie, 2000; Ramankutty et al ., 2002; Kochian et al ., 2004; Yang et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%